Implementation of The PBL (Project Based Learning) Model to Improve Students' Critical Thinking Skills in Science Learning - Fiddaraoini, Nihayatus Saadah; Rosyidiana, Hafidz (Jurnal Multidisiplin Indonesia, 2025)
Science learning is one of the subjects that provides various knowledge about the surrounding nature and its contents, including all objects in nature, events and phenomena that appear there. The use of project-based learning methods in research environments helps students develop their critical thinking skills. This approach involves students in student education by allowing them to investigate problems and find their own answers. This study examines the effect of project-based learning (PBL) on students' capacity for critical thinking using Nonequivalent Control Group Design and using non-probability sampling collection with the Quasi-Experimental Design method. Project-based learning (PBL) encourages students to think critically about their environment by placing them in situations where they must analyze, synthesize, and evaluate data. The PBL model is effective in improving students' academic knowledge and skills such as teamwork and problem-solving. Based on the results of this study, project-based learning is an influential method in improving critical thinking skills.